The implementation of contextual teaching and learning in teaching English - Arianto, Arianto (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2011)
The main purposes of this study are (1) to describe the implementation of contextual teaching and learning (CTL) in teaching English, and (2) to investigate the teacherâs difficulties in implementing CTL in teaching English at the seventh grade students of SMPN-1 Palangka Raya. It was used qualitative method. The subject of this study was an English teacher of SMPN-1 Palangka Raya. It was used observation, interview and documentation to collect the data, and for data analysis it was used data reduction, data display, and conclusion. The findings show that (1) the implementation of CTL implemented by the teacher was through some components of CTL which were applied more frequently than others. The questioning, learning community, and modeling were frequently applied. (2) The problems faced by the teacher were the condition of the students who still made some noise, the large amount of students in the class, little attention from the students, and the shyness from the students to speak up.